“I have to fight for them to investigate things”: a qualitative exploration of physical and mental healthcare for women diagnosed with mental illness - Zirnsak, Tessa; Elwyn, Rosiel; McLoughlan, Grace; Le Couteur, Esther; Green, Chloe; Hill, Nicholas; Roberts, Russell; Maylea, Chris (Frontiers in Public Health, 2024)
Introduction: Women play a significant role in the management of their own healthcare and that of others, however women diagnosed with mental illness and physical health concerns experience significant health inequalities as compared to people living without mental health concerns. Methods: In this paper, we reflect on the experiences of 20 cis women diagnosed with mental and physical health concerns who agreed to be a part of this research. This qualitative study is part of the larger Healthtalk Australia research project which was not gender specific. Female participants shared many experiences of mental and physical healthcare in interviews with researchers that pointed to the need for a gendered approach to addressing health inequalities. Consequently, we iteratively consolidated transcripts of interviews with participants into thematic categories facilitated by NVIVO 12. Results: We identified two broad themes and a set of subthemes: in the doctor's officeexperience of labelling; negotiating medications; and interactions with physical and mental health, and outside the doctor's office -responses to trauma, financial concerns, and reliance on participant's internal resources to get healthcare needs met. Discussion: We conclude that participants in this study undertook significant work to manage their own healthcare needs, despite being challenged by clinicians and systems that failed to see them as whole people with expertise regarding their own health.